1. Pelajaran IPA Materi Menggolongkan Hewan Untuk Meningkatkan Prestasi Belajar Pada Siswa Kelas IV SDN Karangbinangun Tahun Pelajaran 2015/2016 - Zuhro, Saifauz; Rahmawati, Endah (PGSD Universitas WR Supratman Surabaya, 2017)
This study aims to improve student achievement at the fourth grade SDN Karangbinangun subjects of Natural Sciences in animal models classify materials index card match. The main problem to be answered in this study is Bagamaina role of cooperative learning model index card match in science learning materials classify animals can improve student achievement grade IV SDN Karangbinangun the school year 2015/2016. To answering questions that researchers conduct classroom action research conducted by two cycles.The subjects in this study were all students of class IV SDN Karangbinangun a total of 11 students, consisting of eight boys and three female students. This study uses index cards match during the learning of Natural Sciences. Findings from this study indicate that the use of methods of index cards right match will be able to improve learning achievement. Based on research on the first cycle increase in the number of students that can reach as much as 5 KKM students or 45.4%. Cycle II an increasing number of students can achieve as much as 9 KKM students or 81.8%. Based on these data it can be seen that from the first cycle to the second cycle, the rate of increase in the number of students who reached the KKM increased by 4 students, or 36.4%. The data shows that an increase in student achievement from the first cycle and the second cycle.